Infrared Range Sensor Array for 3D Sensing in Robotic Applications. (11th April 2013) - Do, Yongtae; Kim, Jongman
This paper presents the design and testing of multiple infrared range detectors arranged in a two-dimensional (2D) array. The proposed system can collect the sparse three-dimensional (3D) data of objects and surroundings for robotics applications. Three kinds of tasks are considered using the system: detecting obstacles that lie ahead of a mobile robot, sensing the ground profile for the safe navigation of a mobile robot, and sensing the shape and position of an object on a conveyor belt for pickup by a robot manipulator. The developed system is potentially a simple alternative to high-resolution (and expensive) 3D sensing systems, such as stereo cameras or laser scanners. In addition, the system can provide shape information about target objects and surroundings that cannot be obtained using simple ultrasonic sensors. Laboratory prototypes of the system were built with nine infrared range sensors arranged in a 3×3 array and test results confirmed the validity of system.